Experimental Investigation on the Load-Carrying Capacity of Steel-to-Laminated Bamboo Dowel Connection I: Single Fastener with Slotted-In Steel Plate under Tension - Zhaoyan Cui; Liuhui Tu; Ming Xu; Zhongfan Chen; Qingfeng Xu (Advances in Civil Engineering)
The dowel-type connection is widely applied in timber and bamboo structures. It is ambiguous regarding the calculation method of engineered bamboo connections completely referred to the timber design codes. The steel-to-laminated bamboo dowel connections with slotted-in steel plate tests were conducted to investigate the mechanical performance under tension based on the ASTM-D5652-15. The effects of the thickness, dowel diameter, and end distance on the yield load, ultimate load, initial stiffness, and ductility of the connections were studied. The difference in the yield load for different end distance is negligible. With the same thickness of the connections, the lower the thickness to dowel diameter, the larger the load-carrying capacity. The three typical yield modes and corresponding load-displacement curves of the connections are observed. By considering the rigid-plastic model, the theoretical equation for the connections is proposed and proven to fit well with the experimental results. It presents a better prediction for the load-carrying capacity of steel-to-laminated bamboo dowel connections with slotted-in steel plate.